2018
DOI: 10.1248/cpb.c18-00255
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Direct α-Selective <i>N</i>-Glycosylation of Amide with Glycosyl Trichloroacetimidate

Abstract: Through the synergistic catalytic effect of the halogen bond (XB) donor and thiourea catalyst, a direct α-selective N-glycosylation of the amide residue of asparagine derivative was achieved using readily accessible glycosyl trichloroacetimidate. n-Butyl methyl ether was found to be the most suitable solvent for the α-selectivity.Key words glycosylation; organocatalyst; halogen bond; hydrogen bond; green chemistry N-Glycosides are found in a variety of bioactive compounds, including natural products. 1) Sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Finally, halogen bonding to Lewis basic centers of hydrogen-bond donors may enhance the Lewis acidity of the latter . This was realized in a proof-of-principle case by Takemoto et al with a cooperative catalyst system consisting of a 2-iodobenzimidazolium salt as XB donor and Schreiner’s thiourea as HB catalyst .…”
Section: Reactions Involving Xb As Secondary Interaction In Catalysismentioning
confidence: 99%
“…Finally, halogen bonding to Lewis basic centers of hydrogen-bond donors may enhance the Lewis acidity of the latter . This was realized in a proof-of-principle case by Takemoto et al with a cooperative catalyst system consisting of a 2-iodobenzimidazolium salt as XB donor and Schreiner’s thiourea as HB catalyst .…”
Section: Reactions Involving Xb As Secondary Interaction In Catalysismentioning
confidence: 99%
“…For an example Takemoto successfully used organocatalysis for the N-glycosylation using trichloroacetimi-date donors. [8,9] N-Phenyltrifluoroacetimidates have also been used as glycosyl donors for direct N-glycosylation of amides. [10][11][12] O-glycosylation of the amide is though a common side reaction, [13] which has limited the general use of the direct N-glycosylation of amides.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the applicability of XB activation in advancing chemical glycosylations is still in its infancy. Apart from our above mentioned XB-catalyzed strain-release glycosylation 44 , Huber and Codée et al demonstrated a seminal stoichiometric proof-of-principle XB activation in Koenigs-Knorr glycosylation 67 , and recently Takemoto et al described a powerful XB-cocatalytic role to elevate the Brønsted acidity in thiourea for Nglycofunctionalizations and N-glycosylations 68,69 .…”
mentioning
confidence: 95%